2016
DOI: 10.1586/1744666x.2016.1156530
|View full text |Cite
|
Sign up to set email alerts
|

The association between phthalate exposure and atopic dermatitis with a discussion of phthalate induced secretion of interleukin-1β and thymic stromal lymphopoietin

Abstract: Phthalate diesters are widely used as emollients in plastic and cosmetics as well as in food packaging and perfumes, potentially leading to prolonged and repeated dermal, oral and airborne exposure. We here review published articles that have evaluated the putative role of phthalate diesters in the pathogenesis of atopic dermatitis and discuss possible pathogenic pathways. A literature search resulted in 563 articles in Embase and 263 articles in Pubmed. After identification of relevant articles based on scree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Conflicting results were found for an association between exposure to phthalate diester and AE in 5 animal and 12 human studies (3 prenatal and 9 postnatal) . Phthalate diesters are immunomodulatory chemicals in widespread use as plasticizers (added to soften and increase flexibility of plastics) and are also added to some cosmetics and perfumes.…”
Section: Risk Factorsmentioning
confidence: 99%
“…Conflicting results were found for an association between exposure to phthalate diester and AE in 5 animal and 12 human studies (3 prenatal and 9 postnatal) . Phthalate diesters are immunomodulatory chemicals in widespread use as plasticizers (added to soften and increase flexibility of plastics) and are also added to some cosmetics and perfumes.…”
Section: Risk Factorsmentioning
confidence: 99%
“…Several studies (Table 5) revealed that phthalates and the ester derivative are passively ingested from the general environment, foods, drinks, breathing air, and dairy life products, causing various dysfunctions [3,20,30,31,34,[37][38][39][40][41][42][43][44][45][46]. Exposures to DEHP, BBP, DBP, and DEP are associated with dermatitis, conjunctivitis, and allergic symptoms [47]. Other studies have found a relationship of asthma and worsening of pulmonary functions with these phthalates [48].…”
Section: Quantification Of Phthalates In Plastic-based Food Packagingmentioning
confidence: 99%
“…Mechanistically, it appears that phthalates may induce IL-4 and IL-1 family cytokines, which, when taken together, is in line with the T H 2 pro-inflammatory cytokine response seen in AD/AE. 109 However, as with many other environmental exposures, there are studies that find no relationship between developmental phthalate exposure and the development of allergic disease. It is evident that similar to other chemicals used in plastics, such as the more media-hyped bisphenol A, more clinical cohort studies are needed to solidify any links between in utero phthalate exposures and AD/AE development.…”
Section: Environment: Developmental Exposures and Ad/aementioning
confidence: 99%